2002
DOI: 10.4067/s0301-732x2002000100006
|View full text |Cite
|
Sign up to set email alerts
|

Leptospirosis en camélidos sudamericanos. Estudio de prevalencia serológica en distintas regiones de la Argentina

Abstract: Dorta de Mazzonelli y col., 1997; ). From these results, it might be inferred that urine of domestic or wild species which lived with studied camelids, could have been the contagious source.]]>

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 1 publication
1
4
0
1
Order By: Relevance
“…In this study, the prevalence of antibodies against some of the serovars reported in alpacas were high incomparison to those previously reported in cattle fromthe southern highlands (Cachata et al, 2008) and 4 alpaca herds from high elevation in the Department of Puno (Herrera Carpio et al, 2000). The positive reactions observed in alpaca and vicuña, particularly to the serovars icterohaemorrhagiae and pomona, are similar to those found in a survey of 600 alpacas from 30 herds in Canchis Province, Cusco Department, and the District of St. Lucia, Puno Department (Rosadio et al, 2003;Santos et al, 2009), as well as to the finding in a study conducted in llamas and vicuñas from several regions of Argentina (Llorente et al, 2002). The high prevalence, In Peru, leptospirosis is widely distributed in tropical and subtropical regions but has also been detected in the humid sierras of the southern highlands (Céspedes et al, 2006), and several pathogenic serovars including icterohaemorrhagiae, pomona and canicola have been isolated from humans and animals in the central sierra (Liceras de Hidalgo et al, 1989).…”
Section: Discussionsupporting
confidence: 84%
“…In this study, the prevalence of antibodies against some of the serovars reported in alpacas were high incomparison to those previously reported in cattle fromthe southern highlands (Cachata et al, 2008) and 4 alpaca herds from high elevation in the Department of Puno (Herrera Carpio et al, 2000). The positive reactions observed in alpaca and vicuña, particularly to the serovars icterohaemorrhagiae and pomona, are similar to those found in a survey of 600 alpacas from 30 herds in Canchis Province, Cusco Department, and the District of St. Lucia, Puno Department (Rosadio et al, 2003;Santos et al, 2009), as well as to the finding in a study conducted in llamas and vicuñas from several regions of Argentina (Llorente et al, 2002). The high prevalence, In Peru, leptospirosis is widely distributed in tropical and subtropical regions but has also been detected in the humid sierras of the southern highlands (Céspedes et al, 2006), and several pathogenic serovars including icterohaemorrhagiae, pomona and canicola have been isolated from humans and animals in the central sierra (Liceras de Hidalgo et al, 1989).…”
Section: Discussionsupporting
confidence: 84%
“…Leptospirosis is endemic in many countries, including the USA [83][84][85]. In Argentina, seroprevalence of the disease varies between 47.3% and 96.2% in llamas, 0% and 13% in guanacos, and 9% and 62.8% in vicunas.…”
Section: Etiologymentioning
confidence: 99%
“…The presence of seropositive wild camelids (guanacos and vicuna) is particularly important from an epidemiological perspective. The most frequently encountred serovars were copenhageni (serogroup Icterohaemorrhagiae) and castellonis (serogroup Ballum) [84]. Alpacas were shown to react to L. interrogans serovar after vaccination.…”
Section: Etiologymentioning
confidence: 99%
“…Los resultados evidencian seroreacciones en alpacas y vicuñas, particularmente a los serovares icterohaemorrhagiae y pomona en tasas similares identificadas en alpacas de la provincia de Canchis, Cuzco y Santa Lucía, Puno (Rosadio et al, 2003; Santos et al, 2009) y a los CSA domésticos y silvestres de varias regiones de la Argentina (Llorente et al, 2002). La alta prevalencia, particularmente al serovar pomona en las vicuñas muestreadas en el estudio, difiere de lo detectado en 208 vicuñas de la reserva de Salinas y Aguada Blanca (Ortega et al, 2009).…”
Section: Resultados Y Discusiónunclassified